1996
DOI: 10.2105/ajph.86.9.1211
|View full text |Cite
|
Sign up to set email alerts
|

New York inmates' HIV risk behaviors: the implications for prevention policy and programs.

Abstract: In public health, sometimes the farthest distance is the one that is most important to travel. This wisdom is particularly true for efforts to prevent the spread of the human immunodeficiency virus (HIV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 10 publications
2
97
0
1
Order By: Relevance
“…For example, to prevent HIV/STI transmission, prisoners may use plastic gloves and hand lotion instead of lubricated condoms. 24,76 Similarly, to inject drugs, inmates may share needles or "works" or use dirty equipment if sterilization is unavailable. 24,[76][77][78] Moreover, the probability of infection is also higher, since more persons in prisons than in the community are infected with HIV.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to prevent HIV/STI transmission, prisoners may use plastic gloves and hand lotion instead of lubricated condoms. 24,76 Similarly, to inject drugs, inmates may share needles or "works" or use dirty equipment if sterilization is unavailable. 24,[76][77][78] Moreover, the probability of infection is also higher, since more persons in prisons than in the community are infected with HIV.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…24,76 Similarly, to inject drugs, inmates may share needles or "works" or use dirty equipment if sterilization is unavailable. 24,[76][77][78] Moreover, the probability of infection is also higher, since more persons in prisons than in the community are infected with HIV. 27 Overall, there were few racial and ethnic differences in patterns of HIV/STI risk behaviors; most involved the initiation and persistence of substance use among non-Hispanic whites and Hispanics.…”
mentioning
confidence: 99%
“…In these situations, the punk becomes the sexual property of the daddy, who may loan, prostitute, or even sell the punk to others (Brook, 2004;Mahon, 1996;Mariner, 2001;Robertson, 2003). These "protective" relationships constitute a gray area in the literature: Although seemingly consensual, the vulnerable partner enters into the relationship only to avoid sexual exploitation by other inmates.…”
Section: Context Of Prison Rapementioning
confidence: 99%
“…27 In our study, approximately one-third of the population had been incarcerated at least once during the 6 months before the interview, suggesting the importance of correctional facilities as additional sites for intervention to prevent drug injection and other behaviors that increase the risk for HIV infection. 28,29 We found that HIV transmission continued to occur among IDUs who had received both drug treatment and HIV counseling and testing. A need exists for additional strategies to reduce the risk of HIV transmission among IDUs, whether in treatment or out of treatment.…”
Section: Discussionmentioning
confidence: 91%